Teknik Rekayasa Pemadatan Kayu II : Sifat Fisik dan Mekanik Kayu Agatis (Agathis lorantifolia Salisb.) Terpadatkan dalam Konstruksi Bangunan Kayu - Hermantoro .; B. I. Setiawan; S. Hardjoamidjojo; M. H. Bintoro (Jurnal Keteknikan Pertanian, 2003)
The successful application of pitcher irrigation system has motivated to investigate the pitcher as a fetigation system. The experiment was conducted at Leuwikopo Experiment Station, Agricultural Engineering Departemen, Bogor Agricultural University. The main objective of this study is to study the effectiveness of pitcher fertigation system on bushes pepper crops. The result shows that the pitcher wall is capable to release NPK solution. Diffusion rate of fertilizer solution was measured as affected by the concentration inside and outside of the pitcher. The soil moisture distribution in the soil is sufficient to transfor the solution available for crops development. Concentration of Phosphate (P) and Potassium (K) decrease laterally and the Nitrogen (N) tends to accumulate homogeneously in moist part around the pitcher.